THE EFFECT OF LOBEGLITAZONE COMBINATION THERAPY IN TYPE 2 DIABETES - Kim, Yonghyun (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Considering pathophysiology of Type 2 diabetes and glucose lowering effect, metformin and DPP-4 inhibitor combination was the usual first combination therapy option before release of SGLT-2 inhibitor. Adding TZD could be the next best step for delaying progression of diabetes, but TZD is not commonly used because of adverse effect especially in this country. But, we commonly prescribe TZD from the past in our center and after releasing of new TZD drug class in this country, we tried to know the effect of lobeglitazone when it was added in many cases as possible. METHODOLOGY We recruited 244 patients who failed to reach HbA1c target below 7% with metformin and DPP-4 inhibitor from 2016 to 2018. We compared A1c change before and after add-on therapy. RESULTS The mean age and duration of DM was 61.4 and 9.7 years. BMI was 25.7. The mean metformin dose and duration of DPP-4 inhibitor use was 1520 mg per day and 49.1 months each. The HbA1c level before add on therapy was 7.70%. The HbA1c improvement after 6 months was 0.79% and it was greater than after 3 months of 0.69%. The HOMA-IR was 4.12 and it was improved to 3.18 after 6 months. The mean body weight gain after 3 months was 1.02 kg and it was increased to 1.51 kg after 6 months. CONCLUSION Lobeglitazone add on therapy was effective when failed to reach HbA1c target below 7.0% with metformin and DPP-4 inhibitor. The degree was increased after 6 months than 3 months.